Decentering constructs predict experience and tolerance of pain: evidence from a cold pressor study / Constructos relacionados con el descentramiento predicen la experiencia y la tolerancia al dolor: evidencia obtenida mediante la prueba del frío. Issue 3 (2nd September 2019) - DeMarree, Kenneth G.; Naragon-Gainey, Kristin; Giancola, Abigail
Abstract: Decentering is a detached, observer perspective on one's current mental contents. Recent work has identified two potential aspects of decentering, Observer Perspective (OP) and Reduced Struggle (RS), that independently predict the effects of decentering. Specifically, both OP and RS predict reduced psychological distress in response to negative affect, with some variability in predictive utility across outcomes. In this study, we sought to extend previous work by examining OP and RS as predictors of responses to an external source of distress, a painful stimulus. Participants completed measures of decentering, followed by a cold pressor task for up to four minutes. We recorded time that participants were able to withstand the cold-water bath and the intensity of the pain experienced. We found that both OP and RS predicted partiacipants' pain tolerance and pain intensity, but that only RS did so uniquely. Results are discussed with respect to theory on decentering.